Breaking Boundaries: The Representation of Split Identity in Anime - Caroline Ruddell (Animation Journal, 2007)
This article addresses the representation of unstable identity in examples of anime. Split identities in the cinema generally (live action and animation) are often indicative of specific cultural concerns or perhaps mediate contemporary attitudes towards issues of identity in society; the dichotomy that is often apparent in the animation discussed in this paper is that of the past intruding on the present (or even future) and vice versa (which relates to aspects such as technology, urban space, postmodernism and the post-human). For example, modernity and the changing of the world in to a perhaps more global, international, consumerist, even ‘Americanised’ society is a problem that haunts anime and suggests there is still unease that sits with an increasingly modern and consumer-based society; this has implications for both individual identity and the issue of nationality and is expressed in many instances through a split identity, or mapped onto fractured identities in anime. It is also likely, however, that the split subject in anime brings to light many cultural concerns that are transnational, which is arguably bound tightly to the transnational nature of the media industry and increasing popularity of anime internationally. <!–more–> X (1996, Japan) is an anime film (based on a Manga comic) that centres on the problems that occur between the past and present told through two doubled characters. The film tells the tale of Kamui, a young Japanese man who returns to Tokyo in order to fulfil his destiny as protector of Tokyo and everyone who lives there. Kamui must become a Dragon of Heaven and protect the people, while his nemesis will become a Dragon of Earth and will seek to destroy all the people in the world in order to save the planet from destruction. Kamui may take either position initially, and once he has chosen another will take up the opposite position as either protector of people or protector of the Earth. The film introduces the theme of doubling almost instantly as the film opens with the idea that there may be two Kamuis. As the narrative progresses it becomes apparent that Kamui’s friend Fuma takes up his oppositional nemesis position, but he begins to look exactly like Kamui and dresses the same way. Several other characters mention that they find it difficult to tell them apart, and in dream worlds they appear as one and the same person. The film figures the protagonist as embodying very different characteristics split in to two versions of himself: simply put as good and as evil. A divide between good and evil is suggestive of Manichaeism1 which may well derive from Western morality and horror film conventions. It is also worth noting the use of visual devices such as fade-ins in the film that have a distinctly ‘cinematic quality’ and yet the depiction of space and time also smacks of Manga comics2; X demonstrates ‘frozen moments’ and disruption of time and space. By splitting the protagonist in two, the film makes use of the idea of separating one person’s characteristics in to two different bodily entities. However, the film bases this around the dichotomy of the past and present. X places narrative tensions around a split character, but the two halves of this character have very different ideas about the current state of Tokyo (and the world). The good Kamui wishes to save all the people and preserve the world as it is now in the present, while the bad Kamui (Fuma) wishes to kill all the humans on the planet in order to save it by reverting to its former state. X figures the embodiment of the past as an evil force while the figure of the present, and therefore modernity, is represented as good, honest and sincere. While such a Manichean theme seems likely to be deployed in order to appeal to a horror genre audience, perhaps there are further cultural resonating issues at stake. As Paul Wells argues, “different cultural inflections can result in a re-working of the genre which suggests more about the culture in which it is produced […] than the genre itself” (2002, p. 47). In anime the past as a force of evil may stem from the dread that might be apparent in modern Japanese culture of losing older traditional values. Alternatively perhaps by figuring the past as an evil force these films are expressing the pressures that older ways of life put on modern society. It seems likely that both these explanations can describe to a certain extent what is at stake in the past / present binary of this psychological anime film, a binary which is mapped onto problematic issues of identity. By infiltrating the past in to the present a film such as X draws upon the loss of traditional values in contemporary culture. This is perhaps most apparent in cultures such as Japan due to the forced infiltration of Western values in the postwar period into a society that previously upheld tradition over modernity. A link here can be drawn to the cinema in Japan being directly influenced into becoming more ‘modern’ and leaving behind older and more traditional themes by the American occupation. Film production in post war Japan was continuously monitored, as Morton suggests “[m]ovies made in the immediate postwar era were subject to censorship by American occupation authorities and thus period dramas or samurai dramas…were more or less banned on the grounds that they smacked of prewar military ideology” (2003, p. 221). During this period, then, older traditional themes were forcibly removed by American authorities from the cinema screen in order for modernisation to preside. The removal of themes such as the Samurai from the cinema screen was a direct attempt on the part of the Americans to modernise Japan. Modernity and the changing of the world in to a perhaps more ‘Americanised’ or global society is a problem that haunts anime, yet such tensions can also be detected in examples of live-action Japanese films, particularly horror cinema. For example in Ringu [Ring] (1998, Japan) villain Sadako is a ghostly, menacing force from the past who attacks through modern technology in the form of the videotape. Sadako is monstrous and unrelenting in her continual strike at modernity and youth culture; it is largely teenagers who, through hearsay akin to an urban legend, watch the video that curses them to a horrific death within seven days. Such a violent haunting, which is carried out through technology, suggests that there is still unease that sits with an increasingly modern and consumer-based society; this has implications for both individual identity and the issue of nationality. Alistair Phillips argues, for example, that modernity and the past have a rather complex relationship whereby it is more than simply a matter of “a clearly separable set of differences between the old and the new.” (2003, p. 163). Rather the past becomes mediated through the process of modernisation and traditions are “being renegotiated by a new interpretation of a nationally specific modernity” (p. 154). In the live-action Ringu the past, figured as eerie and deadly, is mediated through modern technology. In many anime examples issues related to modernisation are often mapped onto landscapes, which make use of an urban/country dichotomy that can be read as modernity polarised with tradition. Such a discord relates to Japanese culture more generally, for example Buddhism is often regarded as being more prominent in the countryside than in cities. Ian Reader argues that often literature on Buddhism (specifically Zen Buddhism) is: “nostalgic, drawing pictures of idyllic traditional life in the countryside contrasted with the unease of modern, westernised, cities” (1991, pp. 104-105). It seems that, in relation to representation, the past is both nostalgic but also a rather foreboding presence on contemporary times; it could be argued that Reader’s statement suggests that contemporary modern lifestyles in cities moves away from aspects such as religion altogether and away from traditional lifestyles (however they may be defined). Such tensions are not only apparent in fantasy, horror (as in X) or mecha anime, but a children’s anime film such as Sen to Chihiro no kamikakushi [Spirited Away] (2001, Japan) links the nostalgic past with menacing characters and images. The seemingly idyllic space in Spirited Away is at the same time magical and foreboding, filled with spirit and ghosts. The opening of this feature length anime film shows protagonist Chihiro with her parents stopping at a peaceful spot on the way to their new house. Chihiro finds herself in a magical place where witches and spectres roam, where her parents are transformed into animals and where she is often afraid; the site for these events appears to be a serene space with religious statues dotted about in lush scenery. Chihiro’s fear and intrigue is linked to such a space that is untouched and unspoiled by modernisation or industrialisation. In Princess Mononoke San is associated continually with the wolves of the mysterious forest space; she is further linked to the natural world through her animalistic qualities of movement and action, she thinks of herself as wolf rather than human. In Princess Mononoke, while the forest is a magical and untarnished place, it is also rather foreboding and frightening; similarly although the mining colony are destroying the land in the aim of industrialisation they are not depicted as ‘evil’ or villainous. Idyllic countryside locations become polarised with urban, or industrial, environments, and yet in a film such as Princess Mononoke where discord between the two spaces provides narrative drive there is no simple identification of either as ‘right’ or ‘wrong’ (good or evil). In much of Studio Ghibli anime examples the protagonists are also doubled with an animal ‘sidekick’ of some sort, linked to nature, the land and at once idyllic and sometimes menacing spaces3. Animal companions serve to link the protagonists to both nature and childhood. The key point is that such representations appear nostalgic for a time long past, and perhaps lost, yet in many anime examples both images of the past and present are linked with menace and horror as suggested in relation to examples from Studio Ghibli. In X (where due to generic conventions perhaps a Manichean divide is more present) it is the modern urban presence with all it’s advancements that is linked with the ‘good’, not the seemingly tranquil past linked to nature and unspoilt lands. Friction connected to modernisation also relates to live-action film and it is often through a fractured character in some examples of live action that tensions between past and present are articulated, for example the figure of the ghost. In relation to the double, Andrew J. Webber argues that: the Doppelgänger embodies a dislocation in time, always coming after its proper event…[l]ike all ghosts, it is at once an historical figure, re-presenting past times, and a profoundly anti-historical phenomenon, resisting temporal change by stepping out of time and then stepping back in as revenant (Webber, 1996: 9-10) (italics in original) In terms of representation, the tensions between the past and the present in horror, fantasy and psychological genres can be articulated through the process of split characters and the splitting theme, which as Webber points out has a particular relationship to the past and present; through the twinning or doubling of characters a dual representation of the two ideologies of past/present are shown to be at odds and indeed to have specific cultural intimations. In relation to anime, doubling is also apparent in the twinning of characters with animal counterparts (as noted above), or in X where a split character is mapped onto different spaces/timelines, one unspoilt and one modern. However conflict between modernity and tradition is evident in many examples of popular culture; the following analysis of Gin gwai [The Eye] (2002, HK, UK, Singapore) is useful for showing how split identity can be mapped onto past/present tensions in live-action horror cinema. Outlining how fractured identity can be figured in live-action cinema allows for further understanding of how fractured identity is represented in anime. As the film is a co-production from Hong Kong, UK and Singapore it also serves to address the transnational nature of the film industry and question issues of context and nationally specific questions of identity, which will provide a useful point of reference to Japanese animation. The Eye tells the story of a young girl named Wong Kar Mun (Angelica Lee) who, at the age of twenty, undergoes corneal transplants and regains her sight after eighteen years of being blind. Initially it seems that Mun’s surgery has been successful as she gradually regains her sight and begins to adjust to the visual world. She begins therapy with Dr Lo (Edmund Chen) who helps her to interpret what she sees visually rather than relying on touch to find her way around. Soon after her surgery, however, Mun begins to see what she quickly realises are ghosts; it is apparent that she is beginning to witness what the previous owner of her eyes had seen. Mun therefore has a supernatural access to the past. Dr Lo helps Mun to track down the donor of her corneas, Thai-born Ling (Chutcha Rujinanon), whom they discover could foresee death and disaster. Although Ling had tried to help the people in her village by warning them of when something was going to happen, she was treated with hostility by all the villagers and ostracised as a result of her warnings. Only her mother remained kind and supportive of her, although this proved not to be enough and Ling hung herself through desperation of being so isolated, and through devastation at not being able to prevent the disasters she foresees. Mun, then, has in many ways become possessed through her eyes by a figure of the past, and through the narrative the two become twinned or doubled through the connection of Mun’s/Ling’s eyes; Mun and Ling therefore can be seen as an embodiment of the irreparable split between the past and the present. The concept of fracture becomes twofold in this instance: not only is the past/present divide introduced through twin characters, the film hints at all social orders being subject to fracture, fissures and contradictions through this melding of past and present which are essentially irreconcilable. The discordance between the past and the present is a theme that underpins the film, suggesting that there is a tension between older traditions and the contemporary modern world. For example, Mun goes to a teacher to learn calligraphy and her teacher tells her that not many people wish to learn such a traditional style of writing anymore. He had previously taught three classes a week while Mun is being taught on her own, which implies that Mun is his sole student at this time. The scene keys in to the fact that older traditions are being lost in the face of the modern world, which is further driven home by the presence of many ghosts; as figures of the past they perhaps represent a literal embodiment of the loss of particular traditions. The discordance between the past and present works in this live-action film in a similar way to that in the anime example of X where the past is a foreboding presence on contemporary times; Fuma embodies the ideals of a past landscape unspoilt by technology and the human race and he disrupts the modernity of Tokyo through attacking its representative Kamui. In these two examples links between live action and anime can be drawn through the theme of doubling as well as mapping tensions onto a past/present divide. The past/present binary is articulated in a horror film such as The Eye through a splitting of identity mapped across two timelines; this fracture speaks of the fears surrounding a consumerist and modern society and can perhaps be linked to the cultural context that the film was produced in. However, this is problematised by the fact that the film is a co-production and suggests that aspects such as genre also play a role in channelling themes through certain formats. The figure of the ghost is familiar to horror cinema worldwide and through its very nature can be linked to the haunting past. Like the anime examples discussed, as well as ghost narratives such as Dark Water (2002, Japan), The Eye (although produced in a different context) invokes the dread and creeping unease that sits with the loss of the traditional past. Such tensions are arguably relevant globally and are certainly clear in recent anime from Studio Ghibli; tensions surrounding (national) identity are bound in to cultural and national locations to a degree yet are also subject to the global nature of the media industry where genre and narrative conventions, for example, play a key role in shaping examples of the moving image. While in X it is the urban space of Tokyo that is linked with modernity, in many anime examples it is more specifically technology that can be seen as clashing with the traditional past. For example in Akira bodies fuse with technology in a rather terrifying manner. Identity becomes monstrosity in Akira; Napier discusses this in relation to metamorphosis and the antihero Tetsuo, who at times accepts and glorifies in his transformation (2005). Technology is a key factor when thinking about the dualism of characters in anime, as Napier suggests “the fusion of human pilot inside armoured machine leads to bizarre combinations of mechanical/organic violence…” (p. 89). Examples like Akira provide a further dimension of fractured identity in anime; metamorphosis becomes key to the plot and to Tetsuo’s character whose monstrous transformation towards the end of the film blurs any concrete notion of who he is. The representation of such monstrous metamorphosis (related to character identity) is arguably afforded through the medium of animation. Questions of identity in anime are therefore lent further resonance through the fact that they are animated; arguably fractured identity cannot be articulated in quite the same way in live-action film (despite similarities in relation to genre etc). Moist and Bartholow have recently noted that “issues surrounding the status of the individual seem to be especially culturally resonant for Japanese society. In much anime, this general theme is expressed in futuristic tales in which postmodern and post-human themes dominate” (2007, p. 39). Napier posits this preoccupation with apocalyptic themes, which although particularly prominent in anime (which Napier links to post Hiroshima & Nagasaki) is also arguably present in many examples of pop culture internationally. Yet in anime binaries such as human/machine; reality/fantasy; body/mind and body/soul are played with continually (particularly in the fantasy and horror genres). Blurring of divisions is also the case in the highly popular Kôkaku kidôtai [Ghost in the Shell] (1995, Japan/UK) but it is not a source of terror here, rather one of reflection and insight into the ‘human condition’, and what it ‘means’ to be human. Doubling in this film is present in the figure of Major Motoko, a cyborg who is on the trail of the Puppet Master, a high-tech hacker. Themes of identity and psychological issues are articulated through ‘cinematic’ tropes such as reflections in glass or water, as well as the sci-fi narrative of the cyborg figure and problems for remaining ‘human’ in the midst of technological advancement. While the film is often considered solely as a Japanese production due to its anime status, it should also be remembered that it is a joint production with the UK. The film is therefore testimony to the transnational nature of the media business (and the increasing international popularity of anime and Manga) where not only the economic aspects of the industry cross national boundaries, but narrative, stylistics and film form bleed into one another. In live-action cinema of certain genres the double is also articulated through reflective surfaces, for example in Secret Window (2004, USA) the split identity of Mort (Johnny Depp) is made prominent through the use of mirrors throughout the film. Devices such as mirroring are also prominent in classic tales of split identity as in the many renditions of the Jekyll and Hyde story. For example in Dr Jekyll and Sister Hyde (1971, UK) mirrors form a major storytelling device to depict the two differing personalities contained within the one body. This film also links problems with retaining a knowable identity quite specifically with gender identity. More subtly in Ghost in the Shell we have many reflective moments of ‘stillness’ that draw attention to the Major’s preoccupation with self, the body and what it means to be human or not, in essence her ‘life’, soul or ‘ghost’. Her issues with who she is are made apparent with sequences where the Major is inanimate, and some of these sequences last for several frames drawing attention to her psychological state of mind. Ghost in the Shell’s preoccupation with identity and gender identity issues, as well as the use of reflective surfaces and images to depict fragmentary identity, is perhaps suggestive of the cross over of narrative theme and stylistics between cinema globally, but perhaps more importantly also the cross over of theme and narrative between anime and live-action (which is arguably linked to generic traits). In conclusion, Paul Ward argues that animated texts “can represent to viewers not some stylised fantasy world, but reveal something about the world of actuality. The animated worlds depicted are, actually, part and parcel of our world” (2006, p. 114). Ward is discussing animation in relation to documentary, but it seems likely that such an argument extends to anime also; here animation can indeed allow for the ‘real’ to be represented as identity is at times figured as frighteningly fissured, which is arguably metaphorical of how identity can be experienced in the ‘real’ rather than continually ‘whole’ and unproblematic. In terms of experience of identity in the ‘real’, animation allows for expressing fracture in ways that in some instances are similar to live-action film, for example uses of dissolves, fade-ins and reflections in water or glass, as well as generic traits. However, anime also provides differing methods of articulating problematic identity. For example the lavish representation of metamorphosis in Akira is arguably only afforded through the medium of animation, or the intriguingly elongated moments of stillness in Ghost in the Shell that draw on anime stylistics. As Wells suggests “animation is especially persuasive in depicting such states of consciousness – memory, fantasy, dream, and so on – because it can easily resist the conventions of the material world and the ‘realist’ representation that characterises live-action cinema” (2002, p. 49). In anime psychological flux and fracture is a thematic and narrative trope and while articulation of such themes bear similarity to live-action cinema the style of anime also creates a further resonance in relation to the representation of identity. Fractured identity in any form of the moving image invokes a psychological interpretation; narratives based on issues of identity are particularly prominent in anime. All the examples discussed invoke a psychological interpretation because the narrative centres on a splitting or fracturing of a central character, and audiences from many cultures are clearly familiar with such storylines, which is evident in the popularity of the films discussed (at least among the fandom of anime). Psychological reflection and what it ‘means to be human’, in narratives based on split identity, is frequently articulated through the ‘personal’, through a subjective view of what it means to experience ourselves in the world, which in many of these texts (particularly the horror genre) is depicted thematically and narratively as chillingly splintered. Anime allows for understanding identity as not whole through its narrative and generic leanings (and where it departs from these). In the examples discussed, psychological issues are also mapped onto fissured landscapes which provide a comment on national contexts and issues of both individual and national identity. However, the increasingly global nature of the film industry cannot be ignored; while cultural contexts and issues provide an understanding of some of the tensions apparent in these texts, particularly in relation to past and present dichotomies, the transnational qualities of cinema allow for positioning the films discussed in a global context where aspects such as generic conventions are likely to channel issues into certain familiar formats. Notes 1 Manichaeism is a system of belief that invests in the idea that God can only exist in opposition to Satan and vice versa: within such a system one can either be a ‘good’ person or a ‘bad’ person, i.e. good versus evil in horror narratives for example. 2 For more on the tensions between the cinematic and the ‘anime-ic’ see Thomas Lamarre’s 2002 article ‘From animation to anime: drawing movements and moving drawings’ in Japan Forum 14(2), pp. 329-367. 3 For example Kiki has her cat companion Jiji in Majo no takkyûbin [Kiki’s Delivery Service] (1989, Japan) or San is linked with the wolves in Mononoke-hime [Princess Mononoke] (1997, Japan). Caroline Ruddell is Lecturer in Film and Television at St Mary’s University College, University of Surrey, UK. She has written on witchcraft in television with a focus on the use of speech, magical text and identity and her research interests include the representation of identity and subjectivity in film and television; anime and animation studies and film/television theory and methodology. Caroline is a member of the editorial boards for Animation Studies: Online Journal for Animation History and Theory and Watcher Junior: The Undergraduate Journal of Buffy Studies. This paper was initially presented at the Society for Animation Studies Conference in Portland, Oregon in July 2007. References Lamarre, T. (2002), ‘From animation to anime: drawing movements and moving drawings’, Japan Forum, Vol. 14 (2), pp. 329-367 Moist, K. & Bartholomew, M. (2007), ‘When Pigs Fly: Anime, Auterism, and Miyazaki’s Porco Rosso’, Animation: An Interdisciplinary Journal, Vol 2, no. 1, pp. 27-42, Sage Publications Morton, L. (2003), Modern Japanese Culture: The Insider View, Oxford University Press, Oxford Napier, S. (2005), Anime: From Akira to Howl’s Moving Castle, Palgrave Macmillan, New York, Hampshire Phillips, A. (2003), ‘Pictures of the Past in the Present: Modernity, Femininity, and Stardom in the Postwar Films of Ozu Yasujiro’, Screen, Vol. 44, no. 2, Summer, Oxford University Press, Oxford Reader, I. (1991), Religion in Contemporary Japan, Macmillan, Basingstoke Ward, P. (2006), ‘Animated Interactions: Animation Aesthetics and the World of the ‘Interactive’ Documentary’, Animated ‘Worlds’, John Libbey Publishing, Eastleigh Webber, A. J. (1996), The Doppelgänger: Double Visions in German Literature, Clarendon Press, Oxford Wells, P. (2002), Animation: Genre and Authorship, Wallflower Press, London & New York © Caroline Ruddell Edited by Nichola Dobson
Keywords: Anime|split identity|time